Third/fourth degree perineal tear: does anorectal symptoms correlate with manometry and endo-anal scan result? - Abdulwahab, Dalia F; Md Nor, Azmi; Nusee, Zalina; Ismail, Hamizah; Awang, Mokhtar (2014)

(untitled)
Since the introduction of endoanal ultrasound in the early 1990’s. It was found that obstetric anal sphincter injuries (OASIS) rather than neurogenic injury was the leading cause of anal incontinence, where the later can have a devastating effect on a woman’s quality of life (QoL). OASIS is reported in approximately 2.8% of primigravidae and 0.4 % of multigravidae. Despite identification and immediate repair of OASIS, the outcome is still suboptimal. Due to the lack of clear follow up plan and management guidelines following OASIS in many centers, which is remain controversial issue. In this cohort study we assessed the short term outcome of OASIS primary repair which include anorectal symptoms, QoL, sphincter integrity and function and to find the correlation between anorectal symptoms and investigations results